2001
DOI: 10.1103/physreva.65.010501
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the electron affinity of thulium

Abstract: The electron affinity of thulium has been measured using laser photodetachment electron spectroscopy. The electron affinity of Tm(2 F 7/2) was determined to be 1.029Ϯ0.022 eV. The data also show that Tm Ϫ has at least one bound excited state with a binding energy of 0.979Ϯ0.017 eV relative to the ground state of the thulium atom. The present experimental measurements are compared to a recent calculation of the electronic structure of Tm Ϫ and a recent experimental investigation of Tm Ϫ .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 12 publications
9
23
0
Order By: Relevance
“…The results also support the prediction of the formation of Eu − by the attachment of a 6p electron as evidenced by the ensuing (7/2, 1/2) J =3,4 doublet, for which the present measurement indicates a splitting of 0.169 eV. These results are consistent with recent experimental measurements for the electron affinities of praseodymium [20] and thulium [21], whose negative ions are predicted to have an active electron configuration of 4f n 6p, where n is odd. The electron affinities of Pr, Tm and Eu are all near 1 eV and all three negative ions support at least one long-lived, bound excited state.…”
supporting
confidence: 92%
“…The results also support the prediction of the formation of Eu − by the attachment of a 6p electron as evidenced by the ensuing (7/2, 1/2) J =3,4 doublet, for which the present measurement indicates a splitting of 0.169 eV. These results are consistent with recent experimental measurements for the electron affinities of praseodymium [20] and thulium [21], whose negative ions are predicted to have an active electron configuration of 4f n 6p, where n is odd. The electron affinities of Pr, Tm and Eu are all near 1 eV and all three negative ions support at least one long-lived, bound excited state.…”
supporting
confidence: 92%
“…(1) In [2] it was concluded that both the measured and the calculated EAs for the lanthanide atoms Eu [4][5][6][7][8], Tb [9,10], Tm [11,12], Gd [5,10] and Nd [5,6,9], including the Nb [13][14][15][16] atom require reinterpretation. New recommended EA values for these atoms were presented.…”
Section: Introductionmentioning
confidence: 99%
“…This situation is especially true for most of the lanthanide anions except La − and Ce − since the yields of the latter were found three orders of magnitude greater than those of other lanthanide anions14. In early 2000s, a series of measurements of EAs of lanthanides were attempted by Davis and Thompson, including Eu15, Tm16, and Pr17. EAs of ~1 eV were reported for these lanthanides, implying a relatively strong interaction between the extra electron and the neutral.…”
mentioning
confidence: 99%